Spinal fusion surgery for high-risk patients: a review of hospitals information - Mohsen Rasoulivalajoozi; Ghada Touir (Shahid Beheshti University of Medical Sciences, 2023)
Background: Spinal fusion surgery (SFS) is commonly performed as an elective procedure in the United States that employs minimally invasive techniques; however, it possesses potential risks and side effects and is still considered an experimental treatment. As such, patients can often be hesitant when proposed SFS. In that regard, this study aimed to analyze and critique available SFS instructive materials, to account for the procedure's potential risks for patients.   Methods: We have reviewed information concerning surgical procedures and policies (pre-operative to postoperative) on 20 hospitals and medical center websites. All possible keywords regarding SFS were systematically arranged and considered in various ways. The collected data was assessed and compared to identify common themes. Results: Our results indicate that, although some informational sources reaffirm each other's materials, few provided key SFS details, such as potential candidates, outcomes, risks, and aftercare. Moreover, information was neither delivered systematically nor consistently, leading patients to feel anxious, fearful, or confused when making decisions involving SFS. Conclusion: This paper recommends a comprehensive and interactive information system (IS) with a patient-oriented approach, which will facilitate patient decision-making and help people discern between factual data and false information supplied through social media or word of mouth. This information system could then be used for other elective procedures.